Role of Non-Timber Forest Products in Rural Economy of Farmers - Singh, S.; Chaudhary, N.; Bhatia, A. K. (International Journal of Economic Plants, 2020)
Non-timber forest products (NTFPs), also known as non-wood forest products (NWFPs) and secondary forest products are useful substances obtained from forests. The key feature of NTFP’s is the continuous flow of returns against timber returns that are available intermittently at an interval of rotation period. An estimated 80% of the population of the developing world uses NWFP to meet some of their health and nutritional needs. NTFPs provide greater opportunities to the people by providing employment in the lean agriculture season. Most of the activities pertaining to NTFPs like collection, processing, transportation, marketing etc. are labour intensive and provide employment. India holds monopoly in world trade over some of the natural resins and gums such as lac, gum karaya and guar gum. Tribals derive 20-40% of their annual income from minor forest produce on which they spend major portion of their time. It has been established that a number of tribal, rural and forest department communities derive a significant part of their needs, income food and nutrition. The edible NTFPs play an important role in food & nutritional security of rural people. However, due to number of factors like destruction of natural habitat, fluctuating prices, population growth is hindering the development of NTFPs.